The Case for a Carbon Tax Getting Past Our Hang-Ups to Effective Climate Policy - Hsu, Shi-Ling.; SpringerLink (Online service) (Washington, DC : Island Press/Center for Resource Economics : Imprint: Island Press, 2012)
There's a simple, straightforward way to cut carbon emissions and prevent the most disastrous effects of climate change-and we're rejecting it because of irrational political fears. That's the central argument of The Case for a Carbon Tax, a clear-eyed, sophisticated analysis of climate change policy. Shi-Ling Hsu examines the four major approaches to curbing CO2: cap-and-trade; command and control regulation; government subsidies of alternative energy; and carbon taxes. Weighing the economic, social, administrative, and political merits of each, he demonstrates why a tax is currently the most effective policy. Hsu does not claim that a tax is the perfect or only solution-but that unlike the alternatives, it can be implemented immediately and paired effectively with other approaches. In fact, the only real barrier is psychological. While politicians can present subsidies and cap-and-trade as "win-win" solutions, the costs of a tax are immediately apparent. Hsu deftly explores the social and political factors that prevent us from embracing this commonsense approach. And he shows why we must get past our hang-ups if we are to avert a global crisis. In fact, the only real barrier is psychological. While politicians can present subsidies and cap-and-trade as "win-win" solutions, the costs of a tax are immediately apparent. Hsu deftly explores the social and political factors that prevent us from embracing this commonsense approach. And he shows why we must get past our hang-ups if we are to avert a global crisis. In fact, the only real barrier is psychological. While politicians can present subsidies and cap-and-trade as "win-win" solutions, the costs of a tax are immediately apparent. Hsu deftly explores the social and political factors that prevent us from embracing this commonsense approach. And he shows why we must get past our hang-ups if we are to avert a global crisis.
Acknowledgments -- 1. Introduction -- 2. Climate Change Policy Alternatives. Carbon Taxes. Command-and-Control Regulation. Cap-and-Trade. Government Subsidies -- 3. Ten Arguments for a Carbon Tax. One: Economic Efficiency. Two: Excessive Formation of Capital. Three: Non-Interference with Other Regulatory Instruments or Jurisdictions. Four: Government Is Better at Reducing (3z(BBads(3y (BThan Increasing (3z(BGoods(3y(B. Five: Incentives for Innovation$1 (BPrice Effects. Six: Incentives for Innovation$1 (BPrice Breadth. Seven: Administrability. Eight: International Coordination. Nine: Revenue Raising. Ten: Economic Efficiency Revisited: Prices versus Quantities under Uncertainty. Conclusion -- 4. Arguments against a Carbon Tax. Political Economy Considerations. Regressiveness. Ineffectiveness. Crowding Out. Conclusion -- 5. Carbon Tax Psychology. The (3z(BDo No Harm(3y (BEffect. The Identifiability Effect. The Endowment Effect. Conclusion -- 6. Changing Political Fortunes? -- 7. Conclusion -- Endnotes -- Index.s
Keywords: Environmental sciences; Climatic changes; Environmental management; Environmental protection; Economics; Environment; Climate Change; Economics general; Political Science, general; Environmental Management; Atmospheric Protection/Air Quality Control/Air Pollution